Diffusion-Ordered NMR Spectroscopy Application for Analysis of Polysaccharides - N. E. Kuz’mina; S. V. Moiseev; E. Yu. Severinova; A. I. Luttseva (Регуляторные исследования и экспертиза лекарственных средств, 2022)
Diffusion-ordered nuclear magnetic resonance spectroscopy (DOSY) is a molecular transport method in analytical chemistry, based on experimental recording of the molecules’ translational mobility at thermodinamic equilibrium in a solution. The translational mobility is characterised quantitatively by a self-diffusion coefficient. The aim of the study was to summarise the main trends in application of DOSY for the analysis of natural and modified natural polysaccharides used in pharmaceuticals and pharmaceutical biotechnology. The review shows that this method is an effective instrument for monitoring fractionation during isolation of polysaccharides from a natural mixture, for estimating their average molecular weight and molecular weight distribution, and for studying the formation of supramolecular systems based on polysaccharides. The paper describes main issues of the precise measurement of polysaccharide macromolecules self-diffusion coefficients and provides the correction factors to compensate for errors caused by fluctuations in temperature and viscosity of solutions. The observed scatter of self-diffusion coefficients of narrowly dispersed polymer macromolecules nuclei is explained using the polyphase concept. The paper illustrates ways of describing translational mobility of a polyphase polymer macromolecule as a whole. The authors summarise values of the gradient pulse sequence parameters used in quantitative measurements of self-diffusion coefficients of linear, low-branched, and branched polysaccharides.